Ecological Aspects of the Constructing a Nuclear Power Station in Kazakhstan - Abdikarim, Gulzat; Yuldashbek, Davlat; Akhmetov, Nurlan (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
Kazakhstan is rich in natural resources, including coal, oil, natural gas, and uranium, and has significant potential for renewable energy sources, such as wind, solar, hydropower, and biomass. Nuclear energy is often considered an alternative source of energy, capable of reducing the impact on the environment compared to traditional fossil sources such as coal and natural gas. There are currently no operating nuclear power reactors in Kazakhstan. In this context, the potential impact of the planned nuclear power plant in Kazakhstan on the territory and environmental situation of Kazakhstan is considered. However, like any method of energy generation, nuclear energy has its own environmental aspects. NPPs emit almost no other pollutants, such as sulfur (SOx), nitrogen oxides (NOx), and solid particles, which are characteristic of burning fossil fuels. Low carbon emissions: nuclear power plants produce large amounts of electricity with minimal greenhouse gas emissions, which can help combat climate change. High-efficiency nuclear reactors are able to produce a large amount of energy from a relatively small amount of fuel. Uranium-235 and plutonium-239 radioactive elements are often used as reactor fuel. Used in nuclear reactors, they have high energy density. Kazakhstan’s uranium production is carried out exclusively by underground well drilling, which is the most environmentally friendly and least expensive method. Given that Kazakhstan accounts for 40% of global uranium production, it is assumed that transporting reactor fuel could be cost-effective. Stable electricity supply: nuclear plants provide reliable and continuous production of electricity, which makes them important for maintaining the stability of the energy system. Reducing dependence on fossil fuels, the development of nuclear energy can reduce the consumption of coal, oil, and gas, which in turn helps to reduce the negative impact on the environment associated with their extraction and combustion. Long-term energy: nuclear reactors can operate for several decades, which makes them convenient for providing long-term energy needs. The development of waste disposal technologies and research and development in the field of nuclear waste disposal create opportunities for safer handling of them and reduction of negative impact on the environment. These aspects make nuclear energy in Kazakhstan an important part of solving problems in the field of energy, ecology, and economy.